(untitled) (Journal of Asian Development Studies, 2025)
The study explores the entrepreneurial landscape of Pakistan’s creative industries to understand how creative entrepreneurs engage with academic institutions, industry, and government. Institutional fragmentation ought to be an issue in Pakistan, as regulatory fragmentation and weak synergy among academia, industry, and government impede the growth of Creative entrepreneurs. This study applies the Triple Helix Model to the creative sector of Pakistan using a qualitative research method, generating a rare cross-helix dataset (N=34 In-depth Interviews). To ensure interpretative rigor, the study systematically codes data by incorporating grounded theory and thematic analysis. The results highlight various barriers hindering the growth of creative entrepreneurship in Pakistan, including the sector’s informality, policy fragmentation, insufficient institutional-level support mechanisms, an obsolete curriculum, and gender exclusion. Moreover, these results reveal how these barriers act. Academic reports on theory-practice gaps; entrepreneurs report a lack of formal incubators, legal strategies, and capital. Government officials admit to fewer interactions in the sector and in government, and to insufficient inter-departmental collaboration. The theoretical contribution of the study is to contextualize the model for better collaboration in Pakistan’s creative sector, and the practical contribution is to recommend synergistic reforms through the creation of co-designed curriculum reform units, innovation liaison offices, gender inclusion councils, and creative incubators. Recognizing institutional voids and the consequences ascribed gaps, the study provides ways to re-adjust the local institutional space to promote inclusive, deepened THM ecosystems for the advancement of innovation, equity, and sustainable creative entrepreneurship.